A note on integral transforms and partial differential equations - Kilicman, Adem; Gadain, Hassan Eltayeb (Hikari, 2010)
In this study, we apply double integral transforms to solve partial differential equation namely double Laplace and Sumudu transforms, in particular the wave and poisson's equations were solved by double Sumudu transform and the same result can be obtained by double Laplace transform.